Averaging in multifrequency systems with multi-point conditions and a delay - Yaroslav Bihun; Ihor Skutar (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
For multifrequency system of differential equations with a discrete and integral delay we find conditions for the existence and uniqueness of the solution. Linear multipoint conditions are set for the solution. An estimate of the error of the averaging method is obtained, which clearly depends on the small parameter.